The determinant of foreign direct investment in Southeast Asia: Malaysia, Philippines and Thailand / Puteri Iylia Aisyah Mohamad Helmi - Mohamad Helmi, Puteri Iylia Aisyah (Faculty of Business and Management, 2019)
Foreign direct investment has been of large importance in economic growth and global economic integration over the last decades. South East Asia has been part of this development with rapidly increasing inflows of FDI. However, there are large variations over time and between countries in the region as regard to the policies towards FDI, and in actual inflows of FDI. Foreign direct investment is critical for developing and emerging market countries. Their companies need the multinationals funding and expertise to expand their international sales. The purpose of this study is to determine the factors that affecting the FDI for three Southeast Asian countries based on the independent variables, which are economic growth (EGR), exchange rate (EXR), inflation rate (INR) and market size (MKS). The data collected annually from 1978 to 2017 by using panel series data. The data been collected from World Bank Data. The countries that involved in this research are Malaysia, Philippines and Thailand. The data will be measured by using multiple tests like Unit Root test, Pooled OLS test and Regression test. The result shows that exchange rate and market size shown an insignificant positive effect while economic growth and inflation rate shown an insignificant negative effect toward FDI. The result will further the understanding of policymaker and researchers about the important and factors affecting FDI for Southeast Asian countries.